Macrolide Antibiotic in Opioid Detoxification: A Serendipitous discovery? - Aich, TK; Haider, J; Dhungana, M (Journal of Psychiatrists' Association of Nepal, 2019)
Introduction: While receiving opioid detoxification treatment with standard Detoxification protocol, one patient was additionally prescribed Roxithromycin for his associated skin infection. Upon withdrawal of roxithromycin following improvement in skin infection, very next day same patient complained of heightened opioid withdrawal symptoms. These symptoms relieved again following reintroduction of Roxithromycin! Material And Method: It was a naturalistic study of 72 Opioid Dependent patients who received inpatient detoxification treatment at the Universal College of Medical Sciences, Bhairahawa, Nepal. A total of 16 patients received standard opioid detoxification protocol before the incidence of above mentioned patient. Subsequently, a total of 56 patients received Roxithromycin, in addition to the standard protocol, during their inpatient stay with a maximum for a period of 10 days. Necessary ethical clearance from the institute’s ethical clearance committee was taken before carrying out this trial. Duration of inpatient stay and follow-up pattern after discharge was taken as the objective assessment of the efficacy of Roxithromycin in reducing severity of withdrawal symptoms. All other treatment parameters were similar in two groups. Results: Two groups did not differ in most demographic and clinical variables compared. Opioid dependence patients who received Roxithromycin had significantly longer (t=2.5; p=0.01) voluntary hospitalization stay (10.6 days, SD=6.2) vis-à-vis patients who did not receive it (6.4 days, SD=3.9). They also reported significantly more number of follow-ups after discharge (Fisher’s Exact Test= 0.02). Conclusion: Roxithromycin, besides being an antibiotic, also possibly act as an anti-inflammatory and immune-modulatory agent by regulating leukocyte function.